Estimation De L’exhaustivité De La Surveillance Des Intoxications Médicamenteuses Dans La Région De Tanger-Tétouan-Al Hoceima, Maroc, 2014-2016 - Hmimou, Soumaia; Hami, Hinde; Hmimou, Rachid; Soulaymani, Abdelmajid; Mokhtari, Abdelrhani; Soulaymani-Bencheikh, Rachida (European Scientific Journal, ESJ, 2018)
The aim of this study is to estimate the completeness of drug poisoning surveillance in the region of Tanger-Tétouan-Al Hoceima in Morocco. The study deals with cases of drug poisoning identified by the Moroccan Anti Poison Control Center (MPCC) and the cases collected by the registers of the provincial hospitals of the studied region between 2014 and 2016 period. The completeness of the surveillance was studied by the capture-recapture method. During the study period, 835 cases of drug poisoning were identified by the MPCC and 892 cases from the registers of hospitals in the region. The number of duplicates was 78. The capture-recapture method made it possible to estimate the total number of cases at 9 549 (95% CI: 8,199-10,900). The completeness of surveillance is estimated at 8.74% from MPCC and 9.34% from hospital registers in the region. The capture-recapture method provided limited completeness of monitoring for drug poisoning in the study area. Improved awareness of doctors about the declaration is necessary to strengthen the system of surveillance of poisoning in Morocco.